MODEL PENINGKATAN KEUNGGULAN KOMPETITIF MELALUI KINERJA PERUSAHAAN - Fidyah Yuli Ernawati (Jurnal Riset Bisnis Indonesia, 2015)
The purpose of this study was to determine the influence of organizational culture, content strategy,organizational performance either partially or simultaneously to a competitive advantage in PTIndomaret. The method of research using multiple regression analysis with enter method, this researchwas conducted on the territory of Boja and Kendal. The results showed that organizational culturesignificant positive effect on the performance of the organization, content strategy bersignifikan alsoa positive effect on the performance of the organization, and organizational performance significantpositive effect on competitive advantage. In the first equation 76.2%, the variation can be explainedby the performance of the organization by the variable of organizational culture and content strategy,while the second equation 70% of the variation can be explained by the competitive advantage of theorganization’s performance.Keywords: competitive advantage, the company’s performance, organizational culture, contentstrategy.